2001
DOI: 10.1128/jcm.39.8.2954-2957.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Borrelia burgdorferi Isolated from Erythema Migrans Lesions: Interrelationship of Three Molecular Typing Methods

Abstract: Genetic diversity among Borrelia burgdorferi isolates recovered from the skin of Lyme disease patients was assessed by ribosomal DNA (rDNA) spacer restriction fragment length polymorphism analysis, genomic restriction site polymorphism analysis, and plasmid content analysis. There was a significant association between the three rDNA spacer types, the six pulsed-field gel types, and plasmid content (P < 0.001). The association between distinct chromosomal and plasmid markers implies a clonal origin for each gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…(ii) A restriction fragment length polymorphism (RFLP) between the 16S and 23S rRNA genes has been used to categorize isolates into four ribosomal spacer types (RSTs) called RST1, RST2, RST3A, and RST3B. The RST1, RST2, and RST3B groups have been shown to be significantly associated with invasiveness and disease in the mouse model of infection and in humans (46,49,57,58,60,61,103,104,107,108). However, these methods alone cannot always be used to distinguish various B. burgdorferi strains, and these classifications do not contribute at all to determination of the overall plasmid content of the strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) A restriction fragment length polymorphism (RFLP) between the 16S and 23S rRNA genes has been used to categorize isolates into four ribosomal spacer types (RSTs) called RST1, RST2, RST3A, and RST3B. The RST1, RST2, and RST3B groups have been shown to be significantly associated with invasiveness and disease in the mouse model of infection and in humans (46,49,57,58,60,61,103,104,107,108). However, these methods alone cannot always be used to distinguish various B. burgdorferi strains, and these classifications do not contribute at all to determination of the overall plasmid content of the strains.…”
Section: Resultsmentioning
confidence: 99%
“…Before the completion of the sequence of B31, pulsed-field gel electrophoresis (PFGE) was primarily employed in determining the plasmid content of various spirochete strains, even though large circular plasmids are not resolved well in such gels and different linear plasmids often have very similar sizes in the 25-to 30-kb range (8,63,111,112). PFGE is still used to discriminate the plasmid profiles of B. burgdorferi clinical isolates (45,46,84,85), although plasmid loss in culture (see below) can make it an unreliable indicator of relatedness.…”
mentioning
confidence: 99%
“…Also in this study, the 16S-23S rDNA nested-PCR-RFLP typing method, originally used for the typing of B. burgdorferi in clinical specimens from early LB patients (12,17), was extended to include the typing of B. garinii and B. afzelii species directly in field-collected ticks. Only a brief mention of such an approach was found in the literature (17).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were cultivated in BSK-H complete media (Sigma-Aldrich) at 33°C in sealed bottles under 5% CO 2 and were harvested by centrifugation (14,000 ϫ g, 4°C, 20 min). The isolates were obtained from human Lyme disease patients residing in New York and Maryland and have been characterized in previous studies (1,11,22,23,47). Brief descriptions of the isolates employed in this study and their genotypic properties and FH binding abilities are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%